Kyanite Formation and Element Fractionation in the High-Al Eclogites from the Sulu UHP Metamorphic Terrane - Yung-Hsin Liu; Huai-Jen Yang; Jianxin Zhang; Yen-Hong Shau; Mei-Fei Chu; Yoshiyuki Iizuka; Shu-Cheng Yu (Terrestrial, Atmospheric and Oceanic Sciences, 2010)

(untitled)
Eclogite compositions are critical parameters for under standing chemical evolution in the Earth, particularly in subduction zones. A group of eclogites from the Sulu ultra-high pres sure (UHP) metamorphic terrane in eastern China shows uncommon petrographic and compositional features. They are characterized by (1) zoisite porphyroblasts coexisting with inclusion-free, inclusion-containing, and net work kyanite, (2) high Al2O3 of 18.4 - 29.2% with high MgO of 8.59 - 11.3%, and (3) intensive HFSE-REE fractionations represented by [Zr/Sm]ch and [Ti/Gd]ch ratios of 0.1 - 3.9 and 1.1 - 9.0, respectively. High-pressure fluids played a major role on developing these features. Kyanite shows two textural varieties. KyI is inclusion-free and in apparent textural equilibrium with gar net and omphacite, implying formation from plagioclase break down. KyII includes kyanite networks and porphyroblasts; the former occurs mostly in gar net, whereas the latter encloses gar net and omphacite grains. KyII were crystallized at the expense of gar net and omphacite during eclogite-fluid interaction. The low [HREE]ch ratios of 1 - 2 indicate that the protoliths were arc cumulates. The well-de fined in verse Al2O3-SiO2 and Al2O3-CaO correlations are not the characteristics of igneous precursors; there fore, must reflect metamorphic modifications. The comparison to mafic cumulates shows that the low-Al samples are compositionally better representatives of protoliths. Mass balance calculations point to anolivine gabbronoritic protolith. The intensive HFSE-REE fractionations reflect compositional differences between two sample groups. Group I samples have superchondritic HFSE-REE ratios [(Nb/La, Zr/Sm, Ti/Gd)ch = 2 - 7] with depletions in LREE. In contrast, group II samples show HFSE depletions and LREE enrichments. These compositional differences were explained as reflecting element mobility during eclogite-fluid inter action. Released at temperatures > 750°C, the high-pres sure flu ids were enriched in HFSE, REE, and LILE. Upon migration, the flu ids first precipitated HFSE into the group I samples, then, LILE and LREE into the group II samples. This model is sup ported by the occurrence of zoisite porphyroblasts in the group II samples, and interstitial zircon and clusters of small rutilegrains along annealed fractures in the group I samples. Our interpretation for the observed compositional variations implies limited element mobility during subduction and exhumation of continental lithosphere, consistent with existing models, which proposed that the chemical flux to metasomatized mantle wedge is mainly from subducted sediments.